Techniques for Studying Materials, Transmission Electron Microscopy - Goodhew Peter J.; Chivall James; DoITPoMS, University of Cambridge
Este conjunto de animaciones ayuda a entender los principios de la microscopa̕ electrn̤ica de transmisin̤. Est ̀compuesto por los siguientes elementos:A typical TEM systemElectron source of TEMTEM condenser systemFormation of an image by ray diagramsSpherical and chromatic aberrationCondenser lenses in TEM: convergenceTEM: imaging and diffractionTEM projection systemParts of a STEM microscope